Triptycene-trisaroyleneimidazoles as non-fullerene acceptors - Influence of side-chains on solubility, device morphology and performance - Menke, Elisabeth H.; Leibold, David; Lami, Vincent; Hofstetter, Yvonne J.; Mastalerz, Michael; Vaynzof, Yana (Organic electronics, 2017)
The use of non-fullerene acceptors in bulk heterojunction organic solar cells offers the possibility of complementary absorption, adjustment of the electronic energy levels and improved stability and performance. Triptycene-trisaroyleneimidazoles (TTAI) represent a new class of three dimensional acceptor molecules with great promise for application in organic photovoltaic devices. We synthesized six TTAI derivatives in which the molecular symmetry and solubility are varied. We show that these changes do not affect the optoelectronic properties of the acceptor molecules, but have a profound effect on their performance in photovoltaic devices. Enhancing the solubility of the TTAI acceptors to match that of the donor polymer PTB7 resulted in an improved blend phase separation, evident from an enhanced open circuit voltage of 0.9 V and a doubling of the short circuit current as compared to derivatives with lower solubility. A maximum power conversion efficiency of 3.2% was obtained for TTAI with ethylhexyl side chains, demonstrating the potential of TTAI derivatives as electron acceptors.